Iron oxide nanoparticles suppressed T helper 1 cell-mediated immunity in a murine model of delayed-type hypersensitivity - Shen CC (Dove Medical Press, 2012)
Chien-Chang Shen,1,* Hong-Jen Liang,2,* Chia-Chi Wang,3 Mei-Hsiu Liao,4 Tong-Rong Jan11Department and Graduate Institute of Veterinary Medicine, School of Veterinary Medicine, National Taiwan University, Taipei, 2Innovation and Incubation Center, Yuanpei University, Hsinchu, 3School of Pharmacy, Kaohsiung Medical University, Kaohsiung, 4Division of Isotope Application, Institute of Energy Research, Taoyuan, Taiwan*These authors contributed equally to this workBackground: It was recently reported that iron oxide nanoparticles attenuated antigen-specific humoral responses and T cell cytokine expression in ovalbumin-sensitized mice. It is presently unclear whether iron oxide nanoparticles influence T helper 1 cell-mediated immunity. The present study aimed to investigate the effect of iron oxide nanoparticles on delayed-type hypersensitivity (DTH), whose pathophysiology requires the participation of T helper 1 cells and macrophages.Methods: DTH was elicited by a subcutaneous challenge with ovalbumin to the footpads of mice sensitized with ovalbumin. Iron oxide nanoparticles (0.2–10 mg iron/kg) were administered intravenously 1 hour prior to ovalbumin sensitization. Local inflammatory responses were examined by footpad swelling and histological analysis. The expression of cytokines by splenocytes was measured by enzyme-linked immunosorbent assay.Results: Administration of iron oxide nanoparticles, in a dose-dependent fashion, significantly attenuated inflammatory reactions associated with DTH, including the footpad swelling, the infiltration of T cells and macrophages, and the expression of interferon-γ, interleukin-6, and tumor necrosis factor-α in the inflammatory site. Iron oxide nanoparticles also demonstrated a suppressive effect on ovalbumin-stimulated production of interferon-γ by splenocytes and the phagocytic activity of splenic CD11b+ cells.Conclusion: These results demonstrated that a single dose of iron oxide nanoparticles attenuated DTH reactions by suppressing the infiltration and functional activity of T helper 1 cells and macrophages in response to antigen stimulation.Keywords: iron oxide nanoparticle, T cell, macrophage, delayed-type hypersensitivity